Study on etiology of iron deficiency anemia and effect of iron supplementation in women of childbearing age - Al Nasir, Sarah; Nabi Bakeet, Zubaida Abdel; Al Badar, Nawal; Arzoo, Shaista (Progress in Nutrition, 2016)
Summary. Objective: Iron deficiency is the most common nutritional deficiency and is more likely occur at certain times in life such as adolescence, pregnancy and breastfeeding. The main objective of this study is to assess the dietary iron intake, analyze the levels of some iron deficiency biomarkers and to assess the effect of iron supplement (ferrous sulphate) in women of child bearing age living in Al Riyadh. Methods: A structured performa was designed and filled with patients consent to get demographic and health information. Twenty four hour dietary recall method was used for dietary assessment and biochemical tests were performed to analyze the indicators of iron level in serum and to assess the effect of iron supplement (ferrous sulphate) in women of child bearing age. Results: Results shows that 50% subjects were of normal weight and majority of the subjects had enough family income. In this study the dietary intake of iron and vitamin C was far below then the DRI and it was revealed that 27.08% of the subjects were iron deficient as 12.5% of the women’s showed abnormal (lower value) mean cell volume, serum ferritin and transferrin saturation and 14.58% had abnormal serum ferritin and MCV. It was noted that iron supplementation had significant (p≥0.05) effect on total iron binding capacity, transferrin, ferritin, red blood corpuscles and hemoglobin. Conclusion: This study infers that majority of the subjects didn’t have any iron supports. Iron supplementation resulted in improvement in iron status. Nutritional education should be provided to women of childbearing age for increasing nutritional awareness.